Analysing wildfire occurrence through a mixed-method approach: a case study from the Croatian Mediterranean - Jajtić, Kristina; Galijan, Valentina; Žafran, Ivana; Cvitanović, Marin (ERDKUNDE, 2019)
Processes such as littoralization, socio-economic restructuring and agricultural abandonment facilitate land cover changes in the Mediterranean, which then lead to an increased fire risk in the region. These processes are in part driven by people’s values, beliefs and traditional knowledge, lending itself to both qualitative and quantitative research approaches. However, despite the importance of human factors in wildfire occurrence and the complexity of human-environmental relations, such studies so far have been almost exclusively quantitative. This research aims at analysing the drivers of wildfire occurrence in the Mediterranean region of Dalmatia, Croatia through mixed-method approach. Croatia has gone through rapid social and economic changes in the past 30 years which have affected livelihood strategies and landscape configuration. The study includes spatial and statistical analysis of a set of variables during two fire seasons (2011 and 2013), but in-depth interviews with fire-fighters and farmers in the region as well. The results show that grassland and shrubland (maquis) are one of the most important drivers of wildfire occurrence in the region, and that they can be seen as indicators of the process of agricultural abandonment. The research demonstrated differing opinions on the use of agricultural burning in preventing wildfires between farmers and fire-fighters, but a common view of wildfires posing a risk only to human life and material property, disregarding potential risk to ecosystem services.